Effect of acid pretreatment on enzymatic hydrolysis in bioethanol production from rice straw - Aditiya H.B.; Sing K.P.; Hanif M.; Mahlia T.M.I. (Faculty of Engineering, Universitas Indonesia, 2023)
Clean, safe and sustainable energy sources must be found to minimize all side-effects of fossil fuel consumption. Second generation bioethanol possesses a great potential as an alternative energy source especially in the transportation sector. In this study, rice straw was selected to be studied as a conversion of potential lignocellulosic biomass into bioethanol. Firstly, rice straw was processed with mechanical pretreatment using a home blender, followed by acid pretreatment using 2.0 M sulphuric acid (H2SO4) at 90C for 60 minutes. The glucose yield was found to be 9.71 g/L. Then, rice straw pretreated with acid was hydrolyzed using 24 mg of cellulase from Tichoderma Ressei ATCC 26921 over a 72-hour duration, which yielded a total glucose count of 11.466 g/L. After fermentation with Saccharomyces cerevisiae, it was found that by combining enzymatic hydrolysis with acid pretreatment yielded a higher ethanol content after fermentation (0.1503% or 52.75% of theoretical value) compared to acidic pretreatment alone (0.013% or 11.26% of theoretical value). IJTech 2015.